2015
DOI: 10.1371/journal.pone.0142456
|View full text |Cite
|
Sign up to set email alerts
|

TAK-242, a Toll-Like Receptor 4 Antagonist, Protects against Aldosterone-Induced Cardiac and Renal Injury

Abstract: Cardiovascular and renal inflammation induced by Aldosterone (Aldo) plays an important role in the pathogenesis of hypertension and renal fibrosis. Toll-like receptor 4 (TLR4) signaling contributes to inflammatory cardiovascular and renal diseases, but its role in Aldo-induced hypertension and renal damage is not clear. In the current study, rats were treated with Aldo-salt combined with TAK-242 (a TLR4 signaling antagonist) for 4 weeks. Hemodynamic, cardiac and renal parameters were assayed at the indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…In a spinal cord compression injury model, Sprague–Dawley rats were treated with intraperitoneal TAK-242 (TLR4 antagonist), which reduced pain at low doses (Zhang et al. 2015 ; Zhao et al. 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a spinal cord compression injury model, Sprague–Dawley rats were treated with intraperitoneal TAK-242 (TLR4 antagonist), which reduced pain at low doses (Zhang et al. 2015 ; Zhao et al. 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A suspension of microspheres in saline solution containing about 3000 microspheres (42 µm in diameter, Biosphere Medical Inc. Rockland, USA) was injected into the LV during 10s occlusion of the ascending aorta. Rats in the CME plus TAK-242 group received an intravenous injection of TAK-242 (2 mg/kg, MedChem Express, Princeton, USA) via the tail vein 30min before surgery [21], and rats in the sham group received an injection of the same volume of normal saline only.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated that inflammation plays an important role in the pathogenesis of hypertension, and the development and progression of renal fibrosis. 13,36,37 We then assayed the expression of various proinflammatory cytokines by qPCR and ELISA. Figure 1C-F showed that the cardiac mRNA and protein levels of TNF-a, MCP-1, and IL-1β are markedly increased by Aldo infusion, whereas SB-216763 treatment inhibits cardiac inflammatory cytokines levels ( Figure 1C-F).…”
Section: Sb-216763 Suppresses Aldo-induced Cardiorenal Inflammationmentioning
confidence: 99%